Assessing patient use and satisfaction with ankle foot orthoses and service: A cross-sectional study in a tertiary care hospital - Prarthana, Lall Sanya; Pooja, Chauhan; Avijit, Bansal; Gita, Handa (Journal of rehabilitation and assistive technologies engineering, 2025)
The Study was done to examine the use, non-use, the quality of clinical advice, challenges in acquiring AFOs (Ankle Foot Orthosis), and user satisfaction, using a WHO based Rapid Assistive Technology Assessment (rATA) and Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST) questionnaire. The cohort (n = 100) consisted mainly of males (71%) and residents of city (82%). It was found that 98 subjects were under advice from healthcare providers to use an AFO but only 59 subjects were using AFO at present. Common complaints were pain, fitting related and social stigma among users. The majority of the subjects (87%) paid for their AFOs. It was found that the majority of the subjects were “more or less satisfied” with the device however 59% strongly agree that they dislike the appearance of their AFO and 37% were completely dissatisfied with the accessibility of their home and surroundings while using the AFO. It is evident that we should work on improving the design and fit of the orthosis so that the acceptance and satisfaction improves. This study also explores the possibility of usage of rATA for the specific assistive Technology (like AFO in this context) assessment. It was observed that patients often have high expectations regarding a cure with the use of an AFO. Therefore, it is essential for service providers to explain that the AFO is intended to improve function rather than provider a cure. This mismatch of understanding may contribute to dissatisfaction by patients using AFOs, hence user education is essential along with technology provision.